Effect of Gelatin and Citric Acid Concentrations on the Production of Cherry Tomato Jelly Candy (Solanum lycopersicum var. cerasiforme): Effect of Gelatin and Citric Acid Concentrations on the Production of Cherry Tomato Jelly Candy (Solanum lycopersicum var. cerasiforme) - Zahiroh, Alza Della; Azara, Rima (Procedia of Engineering and Life Science, 2023)
This research to determine the effect of gelatin concentration and citric acid concentration on cherry tomato jelly candy products (Solanum Lycopersicum Var. Cerasiforme). The method used in this study was a randomized block design (RBD) using 2 factorials, namely gelatin and citric acid, with 9 treatments repeated 3 times to obtain 27 experimental units. Data analysis was carried out using ANOVA and follow-up tests were carried out with Honest Significant Difference (BNJ) at 5% level while the organoleptic test was analyzed using the Friedman test. The results of this study indicated that the addition of gelatin and citric acid had no significant effect on the reducing sugar of cherry tomato jelly candy, whereas the parameters of water content, ash content, vitamin C had a significant effect on the addition of gelatin and citric acid to cherry tomato jelly candy. The results of this study showed that the highest value for the reducing sugar parameter was 47.70%, the lowest value for ash content was 0.25%, the lowest value for water content was 17.14%, the highest value for vitamin C was 0.50%.